PENGEMBANGAN HANDOUT BERGAMBAR DISERTAI PETA KONSEP PADA MATERI PROTISTA UNTUK SISWA MAN KELAS X SEMESTER 1 - Deviy Akmal, Lucyana; Risdawati, M.Si., Renny; Fitriani, Vivi (Pendidikan Biologi, 2014)
ABSTRACT Handout is teaching material that is give to students for learning process. Teacher can make it from literatures which have relevance with basic competence of students. Based on observation had been done in MAN Sangir, South Solok Regency. It was found that they rarely used handout in teaching learning process. They only used common textbook which has uninteresting pictures. Student should understand the concept of the material by using mind map. The aim of this research was to produce a pictorial handout with mind map in protista material that is valid and practical. This is development research which consist of 4-D models, they are define, design and develop. Furthermore, the primary data is taken from lecturers, teachers and students. The data was analyzed by using descriptive analysis. The result of research produced handout which has validity 85,65%. That was determines from didactic, construction and technique. Then, practical criteria of it were 88% from teacher and 80,83% from students. It was determine from handout  forms,  contents  and  motivation.  Therefore,  learning  media  which  is  constructed  in pictorial handout that completed with mind map for teaching and learning process of protista that was produced was valid and practical.